Factors Influencing the Quality of Life in Patients with Chronic Kidney Failure Subject To Hemodialysis - Insfrán, José Luis Gamarra; Dias, Renato Soares Sanches; Sanches, Cristina José Fernandes (International Journal of Innovative Research in Medical Science, 2021)
Introduction: The patient with terminal chronic renal insufficiency in treatment with Dialysis, usually undergoes psychological and social changes, in his lifestyle and also in his spiritual life, which not only affect him, but the whole family of the. For this reason, it is essential to study the quality of life of this type of patient, since it allows us to analyze to what extent a patient's life is affected by the different interventions they require and by the damage caused by the disease and treatment. Objective: To describe the factors that influence the quality of life of patients with chronic renal failure undergoing hemodialysis in nephrology services. Materials and methods: A descriptive, retrospective and cross-sectional study was undertaken. Results: The research allowed determining that in the group of patients under study predominates: the older adult age range, married, presence of family support network, with complete basic education, of urban origin, with more than two pathologies associated with patient and in treatment for a period greater than one year. According to the Areas of the SF-36 health questionnaire, the Functional State Area is perceived as from Fair to Poor (90%); the Welfare Area as Good (70%), the General Health Perception as Good to Fair (92%) and the Health Change over time as Good to Fair (55%). Conclusion: In general, it was concluded that the perception of quality of life is Good. The factors considered to have an influence on this perception are: education, presence of a support network, marital status, origin, associated chronic pathologies and time on hemodialysis.